Analisis Beban Kerja Mental Menggunakan Metode NASA Task Load Index (NASA-TLX): Sebuah Tinjauan Literatur - Meisal Maulana; Widya Retno Prasinta; Abdul Rojak; Anwar Samsa (Indo Publishing, 2026)
Mental workload is one of the ergonomic factors that can affect workers' performance, productivity, and well-being in the manufacturing industry. High job demands, time pressure, and the need for sustained concentration may increase the mental workload experienced by operators. Therefore, an appropriate method is required to measure mental workload systematically and objectively. This literature review aims to analyze the application of the NASA Task Load Index (NASA-TLX) method in assessing mental workload across various industrial sectors and to identify the dominant dimensions influencing workers' mental workload. This study employed a Systematic Literature Review (SLR) approach by analyzing a number of journal articles and references related to mental workload assessment using the NASA-TLX method. The findings indicate that NASA-TLX is widely used because it evaluates six dimensions of workload, namely Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration Level. Based on the synthesis of previous studies, the mental workload of industrial workers is generally classified as high, with Mental Demand, Effort, and Temporal Demand identified as the most dominant dimensions. High mental workload is mainly influenced by task complexity, production targets, time constraints, and the need for sustained concentration. These findings demonstrate that NASA-TLX is an effective method for identifying the sources of mental workload and can serve as a basis for improving work systems, enhancing ergonomics, and optimizing human resource management. Furthermore, this review provides insights into the potential application of the NASA-TLX method for analyzing the mental workload of electric tricycle assembly line operators at PT Pindad.